Selective deoxygenative alkylation of alcohols via photocatalytic domino radical fragmentations - Hong-Mei Guo (Nature Portfolio, 2021)
The generation of alkyl radicals through deoxygenation of abundant alcohols via photoredox catalysis is of interest. In this study, the authors report a one-pot strategy for visible-light-promoted photoredox coupling of alcohols with electron-deficient alkenes, assisted by carbon disulfide and triphenylphosphine.